1974
DOI: 10.1002/bip.1974.360131105
|View full text |Cite
|
Sign up to set email alerts
|

Conformational behavior of poly‐N5‐(3‐hydroxypropyl)‐L‐glutamine in water–methanol mixtures studied by 13C nmr and CD spectroscopy

Abstract: SynopsisThe helix-coil transition of poly-N~-(3-hydroxypropyl>~-glutamine (PHPLG) has been studied in methanol-water by CD and cmr spectroscopy. For polydisperse PHPLG, two separate peaks arising from residues in helical and random-coil conformations are observed during the transition for both main-chain carbons. These results are discussed and compared to those observed in the case of a polymer sample obtained by racemization of PHPLG in 0.1 M NaOH and of PHPLG samples of controlled molecular weight and dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…25 They have shown that lowmolecular-weight poly[N5-(3-hydroxy propy1)~-glutamine] in water/ methanol mixtures exhibits peak doubling in the carbon-13 nmr spectrum. On fractionation, the double-peak character is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…25 They have shown that lowmolecular-weight poly[N5-(3-hydroxy propy1)~-glutamine] in water/ methanol mixtures exhibits peak doubling in the carbon-13 nmr spectrum. On fractionation, the double-peak character is reduced.…”
Section: Resultsmentioning
confidence: 99%